A computer‐aided methodology to design safe food packaging and related systems. Issue 4 (6th March 2013) - Nguyen, Phuong‐Mai; Goujon, Audrey; Sauvegrain, Patrick; Vitrac, Olivier
<x xml:space="preserve">Abstract</x> A specific "Failure Mode, Effects, and Criticality Analysis" (FMECA) methodology has been developed to detect substances, materials, and steps that are critical for the safety of packaging systems used in food contact and related applications. Contamination levels in the finished product beyond acceptable thresholds are screened via a systematic analysis of crossed mass transfer between components and a serialization of mass‐transfer instances during product lifetime. The whole framework, including physical modeling and expert systems, has been integrated within the open‐source simulation software FMECAengine. The whole approach is illustrated on three case studies representative of applications along the food packaging supply chain: (1) identification of critical routes of the contamination by printing ink constituents, (2) concurrent engineering of multipurpose packaging, and (3) application to surveys or control plans. The implementation of this framework within industrial commitments such as compliance with EU regulations and ISO 22000 type food safety management systems is discussed. © 2013 American Institute of Chemical Engineers AIChE J, 59: 1183–1212, 2013